Liver sinusoidal endothelial cell expressed vascular cell adhesion molecule 1 promotes liver fibrosis - Guo, Qianqian; Furuta, Kunimaro; Islam, Shahidul; Caporarello, Nunzia; Kostallari, Enis; Dielis, Kobe; Tschumperlin, Daniel J.; Hirsova, Petra; Ibrahim, Samar H. (Frontiers in Immunology, 2022)
Background: During liver injury, liver sinusoidal endothelial cells (LSECs) dysfunction and capillarization promote liver fibrosis. We have previously reported that the LSEC vascular cell adhesion molecule 1 (VCAM1) plays a key role in liver inflammation in nonalcoholic steatohepatitis (NASH) and we now aim to uncover its role in LSEC capillarization and liver fibrosis. Methods: Wild-type C57BL/6J mice were fed either chow or high fat, fructose and cholesterol diet to induce NASH and treated with either anti-VCAM1 neutralizing antibody or control isotype antibody. Inducible endothelial cell-specific Vcam1 deleted mice (Vcam1Δend) and control mice (Vcam1fl/fl) were fed choline-deficient high-fat diet (CD-HFD) to induce NASH or injected with carbon tetrachloride to induce liver fibrosis. LSECs isolated from Vcam1fl/fl or Vcam1Δend and hepatic stellate cells (HSCs) isolated from wild-type mice were cocultured in a 3-D system or a μ-Slide 2 well co-culture system. Results: Immunostaining for Lyve1 (marker of differentiated LSECs) was reduced in Vcam1fl/fl mice and restored in Vcam1Δend mice in both NASH and liver fibrosis models. Co-immunostaining showed increased α-smooth muscle actin in the livers of Vcam1fl/fl mice in areas lacking Lyve1. Furthermore, scanning electron microscopy showed reduced LSEC fenestrae in the Vcam1fl/fl mice but not Vcam1Δend mice in both injury models, suggesting that VCAM1 promotes LSEC capillarization during liver injury. HSCs profibrogenic markers were reduced when cocultured with LSECs from CD-HFD fed Vcam1Δend mice compared to Vcam1fl/fl mice. Furthermore, recombinant VCAM1 activated the Yes-associated protein 1 pathway and induced a fibrogenic phenotype in HSCs in vitro, supporting the profibrogenic role of LSEC VCAM1. Conclusion: VCAM1 is not just a scaffold for leukocyte adhesion during liver injury, but also a modulator of LSEC capillarization and liver fibrosis.